Peningkatan Literasi Budaya pada Mata Pelajaran Pendidikan Pancasila Siswa Kelas IV SDN Sendangmulyo 02 Berbantu Media Wordwall - Putri, Sya``rifah Dwi Saputri; Filia Prima Atharina; Husni Wakhyudin; Yenny Rachmawati (Prosiding Seminar Nasional Pendidikan Profesi Guru, 2025)
This study aims to improve students’ cultural literacy through the implementation of Wordwall media in Pancasila Education learning for fourth-grade students at SD Negeri Sendangmulyo 02. The background of this research is based on the low involvement and understanding of students regarding cultural diversity due to conventional learning methods. This study employed a Classroom Action Research (CAR) method conducted in two cycles. The research subjects were 28 fourth-grade students. Data were collected through observation and questionnaires. The results showed an increase in students’ cultural literacy, from an average of 32% in the pre-cycle, rising to 56% in the first cycle, and reaching 84% in the second cycle. In addition, the questionnaire results at the end of the second cycle reached 88%. The use of Wordwall media effectively created engaging, interactive learning, increased students’ confidence, participation, and awareness of cultural diversity. Therefore, Wordwall media can be considered an alternative interactive learning strategy in Pancasila Education at the elementary school level.